When Fatwa Meets Algorithm: Unraveling The Ethics and Law of Digital Da’wah and Islamic Counseling - Alimatul Putri, Nadila; Khoiroti, Shonia Malikah (Proceedings Of International Conference On Islamic Counseling Studies (ICONICS), 2025)
The digital era has fundamentally transformed the landscape of Islamic da’wah and counseling. This study explores how technological advancements particularly the emergence of social media, video platforms, and artificial intelligence have reshaped the way Islamic messages are communicated and how ethical challenges arise from this transformation. Using a qualitative descriptive method through library research, this study analyzes the dynamics between fatwa (traditional religious authority) and algorithms (digital authority) as dual forces influencing the dissemination of Islamic teachings in the digital age. The findings reveal that while digital media such as YouTube, Instagram, and other online platforms expand the reach of da’wah and provide accessibility for online counseling (cyber counseling), they also introduce new ethical and moral challenges, including misinformation, commercialization of religious content, and reduced interpersonal interaction. The integration of Islamic ethical principlessuch as amanah (trustworthiness), hikmah (wisdom), and akhlaq (morality)is therefore essential to maintaining the authenticity and spiritual depth of digital da’wah and counseling practices. Ultimately, this study concludes that the synergy between fatwa and algorithm, ethics and technology, can enhance the effectiveness of Islamic da’wah and counseling by promoting moral integrity, digital literacy, and spiritual resilience in modern Muslim society.